Integrated Approach of Risk Sensitive Land Use Zoning: A Case Study of Banepa Municipality - Dahal, Lekh Nath (Journal on Geoinformatics, Nepal, 2017)
Land is a basic source of livelihood for most of the Nepalese. Land fragmentation, improper use of land, rapid urbanization and lack of formal plan has created serious problems mostly in urban areas including study area. So proper Land use planning is necessary for getting optimum benefit from land resource in sustainable way. Risk factor has to be considered in land use planning process. Since Expert driven (Top down) approach has not gained satisfactory achievement, Participatory (Bottom up) approach has emerged to ensure public participation in land use planning. Participatory approach has also some limitations. So the study seeks to implement integration of both expert driven and participatory approach to identify low risk land use zones in study area. Study targeted to identify risk areas from participatory approach before land use zoning. The case study was carried out in Banepa Municipality. The research was completed by following integrated approach using both primary and secondary data. Both desk study and case study method has been applied. Questionnaire, focus group discussion, interview techniques has been used in the study for collecting primary information where as high resolution satellite imagery, municipal GIS database, Census data etc. were used as secondary data. GIS application was used for Multi-criteria Analysis (MCA). To determine corresponding weight for each factor for land use zoning AHP (Analytical Hierarchy process) has been implemented. Different risk zones in the study area are identified using participatory approach. Final risk free land use zoning map of the study area is prepared. Study concludes that integrated approach is useful for effective land use zoning and risk should also be considered in this process. Different kinds of risk like landslide, flooding, industrial hazard etc. are dominant in the study area. Legal, organizational and technical improvement is required for effective implementation of land use zoning.